Pengaruh media sosial terhadap sosialisasi remaja di era digital - Damayanti, Aulia; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research seeks to examine how social affects the socialization process of adolescent in the contemporary digital age. The rapid advancement of information technology has transformed patterns of social communication, especially among teenagers who are active social media users. This research employs a library research method by reviewing relevant academic literature. The findings indicate that social media exerts a dual influence on adolescent socialization. Positively, it expands social networks, enhances creativity, and serves as a medium for learning and character development. Conversely, excessive use may lead to psychological disorders, reduced face-to-face interactions, and deviant behaviors such as cyberbullying and hedonism. Efforts to optimize adolescent socialization in the digital era can be achieved through parental supervision, digital literacy education in schools, and the cultivation of responsible online ethics.